Akhlak dan Ilmu Pengetahuan: Relasi, Tantangan, dan Implikasi di Era Modern: Morals and Sciences: Relations, Challenges, and Implications in the Modern Era - Husnul Khotimah; Fahmi Darusti; Rahmatullah Rahmatullah; Muhammad M Ahdad (Madrasah Tsanawiyah DDI Cilellang, 2024)
The relationship between ethics and scientific knowledge has significant consequences for education and community development in the 21st century. Rapid technological advances and globalization have resulted in value abrasion (the erosion of religious and national cultural values). This study starts from the idea that rapidly developing science without a moral basis risks causing value disorientation and misuse of science. The purpose of this study is to analyze the conceptual relationship between morality and science, the challenges of integrating moral values in the scientific process, and the ethical implications of modern technological innovations, such as artificial intelligence and biotechnology. This type of research is a Systematic Literature Review (SLR) with inclusion criteria: scientific journals that discuss ‘the relationship between morality and science’ and ‘challenges and implications in the modern era’, published in 2015-2024, indexed by Google Scholar, and indexed by the Science and Technology Index (SINTA). The results show that separating science and morality can cause a humanitarian crisis, but combining the two can be the basis for sustainable, civilized progress. Therefore, it is necessary to recontextualize education and scientific practices based on universal ethical values. This research has implications for the importance of building a broad scientific paradigm that not only prioritizes profit and truth but also has moral responsibility.